Pluralistic Historical Narratives and Their Implications for History Education: A Case Study - Een Syaputra (Southeast Asian Journal of Global Trends and Issues in Education, 2025)
The diversity of historical narratives in Indonesian historiography poses distinct challenges for history teachers, particularly in deciding whether to present the official or alternative interpretations. This study discusses the PRRI movement as a case of narrative pluralism in Indonesian history. It seeks to answer three central questions: (1) how PRRI is portrayed within the official historical narrative; (2) how alternative narratives interpret PRRI’s history; and (3) what implications these differing perspectives hold for history education in schools. The findings reveal that, in the official narrative, PRRI is depicted as an act of regional disobedience, resistance, and betrayal, particularly by West Sumatra, against the central government. Conversely, in several counter narratives, PRRI is interpreted as a regional corrective movement toward what was perceived as the central government’s inequitable development policies, without any intention of secession from the Republic of Indonesia. This plurality of narratives has significant implications for history instruction, requiring teachers to maintain strict neutrality and objectivity. Educators are encouraged to present balanced, evidence-based perspectives and to use emancipatory questioning strategies to enhance students’ critical and historical awareness.